May inflammatory markers be used for monitoring the continuous positive airway pressure effect in patients with obstructive sleep apnea and arrhythmias?. (June 2018) - Dediu, G.N.; Diaconu, C.C.; Dumitrache Rujinski, S.; Iancu, M.A.; Balaceanu, L.A.; Dina, I.; Bogdan, M.
Abstract: Introduction: Obstructive sleep apnea syndrome (OSAS) is defined by recurrent episodes of significant reduction or absence of the oro-nasal airflow during sleep, in the presence of thorax and abdominal movements and snoring. The pathophysiological consequences of intermittent hypoxia determined by OSAS are represented by systemic inflammation, the release of free oxygen radicals and activation of the sympathetic nervous system. Cardiac arrhythmias are a frequent comorbidity in patients with OSAS. Hypothesis: We hypothesized that the continuous positive airway pressure (CPAP) therapy has an effect on inflammatory markers (erythrocyte sedimentation rate, fibrinogen, and red cell distribution width) in patients with OSAS and cardiac arrhythmias. Evaluation of the hypothesis: We tested this hypothesis on 52 patients diagnosed with OSAS and cardiac arrhythmias, divided into two groups: group A (patients who received CPAP therapy and pharmacological therapy) and group B (only pharmacological therapy). The patients were evaluated at enrollment (T0), at 3 and 6 months. We did not find a statistically significant difference of erythrocyte sedimentation rate (ESR) and fibrinogen levels between the two groups. Regarding the red cell distribution width (RDW), the CPAP treatment seems to have improved the RDW values in patients who received this treatment. Also, in patients from group A, a significant decrease in the average heart rate was noticed after 3 months. Consequences: Fibrinogen and ESR cannot be used for monitoring the CPAP therapy in patients with OSAS and arrhythmias. Instead, the beneficial effect of CPAP in patients with OSAS and cardiac arrhythmias can be monitored with the help of the RDW, which could also be used for evaluating the cardiovascular risk in patients with OSAS and arrhythmias.